Preventing mental illness through existential principles - Wetzel, Janice Wood (Journal of religion and health, 1980)
A case is made for the dysfunctional attributes of traditional marital relationships conceptually based upon the material principle of scarcity. The application of the existential principle of abundance is put forth for the purpose of developing genuine mutual support, personal awareness, and authenticity leading to the prevention of mental illness.